2015
DOI: 10.33119/kkessip.2015.3.3.5
|View full text |Cite
|
Sign up to set email alerts
|

Are Beta Parameters Stable on the Warsaw Stock Exchange?

Abstract: Beta parameter is one of the commonly used measurements of individual stockor portfolio investment risk and plays a crucial role in modern portfolio theoryparticularly in management of financial investment portfolios. Many studieshave been done in this field, particularly on its properties such as stability in thecontext of the stock market cycle phases, measuring frequency of rate of return,length of sample period. However, the number of studies concerning beta parameterin the counties of Central and Eastern … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
(4 reference statements)
0
1
0
Order By: Relevance
“…In turn, analysis of Sunder (1980), Bos and Newbold (1984) and Braun et al (1995), all for NYSE, showed that beta coefficients are highly timevarying. At last, some empirical studies produced contradictory result on the stability of beta on developed markets, just like for emerging markets, e.g., Baesel (1974), Levy (1971), Dębski et al (2011), Dębski and Feder-Sempach (2012), Witkowska (2008).…”
Section: Stability Of Beta Coefficient Of Emerging Markets -Literature Reviewmentioning
confidence: 99%
“…In turn, analysis of Sunder (1980), Bos and Newbold (1984) and Braun et al (1995), all for NYSE, showed that beta coefficients are highly timevarying. At last, some empirical studies produced contradictory result on the stability of beta on developed markets, just like for emerging markets, e.g., Baesel (1974), Levy (1971), Dębski et al (2011), Dębski and Feder-Sempach (2012), Witkowska (2008).…”
Section: Stability Of Beta Coefficient Of Emerging Markets -Literature Reviewmentioning
confidence: 99%